Investment Climate Assessment of Bhutan : Removing Constraints to Private Sector Development to Enable the Creation of More and Better Jobs - Santini, Massimiliano; Tran, Trang Thu; Beath, Andrew (World Bank, Washington, DC, 2017)
The 2017 Investment Climate Assessment of Bhutan provides a detailed assessment of firm performance and constraints as they enter, operate, and exit domestic and international markets. The report provides policy recommendations that will support Bhutan to achieve an investment climate conducive to private sector growth, and the creation of productive and gainful employment.